Increasing Value Delivery in Horticulture Sector in Indonesia Tedy Herlambang - Tedy Herlambang (Universitas Panca Marga Probolinggo, 2019)
This paper addresses how to deliver more value in horticulture supply chain in Indonesia for consumers are demanding high quality product, healthier and environmentally friendly. Meeting such demand change is possible if all participants in the chain closely collaborate to develop new product and/or explore new market. Likewise, investment in research and development to improve crops quality, presentation, packaging and create market opportunities within existing outlets and new areas is deemed important. Key words: horticulture supply chain, value, quality